Research on piano teaching and education for the elderly in China - Ning, Fan; Pattananon, Nicha; Rodchangphuen, Pakorn (Journal of Roi Kaensarn Academi, 2024)
The main function of piano teaching for the elderly is to meet the needs of those who have retired and are at a loss to regain self-confidence and improve self-esteem. The study of the old people in the university makes them find the meaning of life again, and the study of the piano makes them realize their self-worth. Therefore, education for the elderly is more inclined to part-time education, and the elderly group pays more attention to their own lives. Those requirements and goals for the profession are less important or almost no requirements. This article presented Research on piano teaching and education for the elderly in China.